Parents' Experience in Providing Support and Motivation to Children in Conflict with the Law Undergoing Rehabilitation During the Time of the Covid-19 Pandemic - Muhammad Abduh; Adi Fahrudin; Husmiati Yusuf; Erik Saut H. Hutahaean (Asian Social Work Journal, 2023)
This study aims to explore the experiences of parents and the obstacles they experience in providing support and motivation for children undergoing rehabilitation during the Covid-19 period at LPKA Class II Jakarta. This study uses a qualitative research method - descriptive. The results of this study are that there is compatibility in several aspects of parental support given to their children who are undergoing rehabilitation at LPKA Class II Jakarta during the Covid-19 period, including (1) having time with family) having good communication between family members; (3) mutual respect among family members; and (4) there is a close relationship or bond between family members. The motivation given by parents is to try to bring bathing warmth to the family which ultimately raises motivation in children to be better. Meanwhile, the obstacles faced by parents include (1) fluctuating signal conditions, (2) time constraints, (3) limited internet quota filling costs, (4) unable to attach children directly, and (5) the child's response.